The protective role of GLP-1 in neuro-ophthalmology - Sohum Sheth; Aashay Patel; Marco Foreman; Mohammed Mumtaz; Akshay Reddy; Ramy Sharaf; Siddharth Sheth; Brandon Lucke-Wold (Exploration of Drug Science)
Despite recent advancements in the field of neuro-ophthalmology, the rising rates of neurological and ophthalmological conditions, mismatches between supply and demand of clinicians, and an aging population underscore the urgent need to explore new therapeutic approaches within the field. Glucagon-like peptide 1 receptor agonists (GLP-1RAs), traditionally used in the treatment of type 2 diabetes, are becoming increasingly appreciated for their diverse applications. Recently, GLP-1RAs have been approved for the treatment of obesity and recognized for their cardioprotective effects. Emerging evidence indicates some GLP-1RAs can cross the blood-brain barrier and may have neuroprotective effects. Therefore, this article aims to review the literature on the neurologic and neuro-ophthalmic role of glucagon-like peptide 1 (GLP-1). This article describes GLP-1 peptide characteristics and the mechanisms mediating its known role in increasing insulin, decreasing glucagon, delaying gastric emptying, and promoting satiety. This article identifies the sources and targets of GLP-1 in the brain and review the mechanisms which mediate its neuroprotective effects, as well as implications for Alzheimer’s disease (AD) and Parkinson’s disease (PD). Furthermore, the preclinical works which unravel the effects of GLP-1 in ocular dynamics and the preclinical literature regarding GLP-1RA use in the management of several neuro-ophthalmic conditions, including diabetic retinopathy (DR), glaucoma, and idiopathic intracranial hypertension (IIH) are discussed.